Association between individual response to food taste and gastroesophageal symptoms. Issue 6 (June 2015) - Shibata, Tomoyuki; Nakamura, Masahiko; Omori, Takafumi; Tahara, Tomomitsu; Ichikawa, Yuichiro; Okubo, Masaaki; Ishizuka, Takamitsu; Nakagawa, Yoshihito; Nagasaka, Mitsuo; Nakamura, Masakatsu; Arisawa, Tomiyasu; Hirata, Ichiro
<x xml:space="preserve">Abstract</x> Objective Taste is an important element in food preferences. Gastroesophageal reflux disease (GERD) is related to lifestyles including eating habits. We aimed to investigate the relationship between responses to specific tastes and GERD. Methods Altogether 280 patients including 170 men with a mean age of 58.6 years were included in the study to determine the relationship between their liking for specific tastes and GERD using a new self‐administered questionnaire (responses to various tastes and participants' sensitivity to taste and hot food and on the frequency of stomatitis). Another self‐administrated questionnaire was administrated for a diagnosis of GERD (the frequency scale for the symptoms of GERD cut‐off score of 10). Furthermore, 142 of 280 patients who had received esophagogastroduodenoscopy (EGD) were investigated on the association between endoscopic esophagitis and their favorite tastes. Results In the association analyses between responses to specific tastes and GERD, the group liking salty food and the group with a high frequency of stomatitis had a significantly higher incidence of GERD (salty food: odds ratio [OR] 2.059, 95% confidence interval [CI] 1.215–3.488, P = 0.0073; stomatitis: OR 2.861, 95% CI 1.558–5.253, P = 0.0007, respectively). In association analyses with endoscopic esophagitis, the groups liking salty and sour food had a significantly higher incidence rate of endoscopic esophagitis (salty: OR 2.718, 95% CI 1.330–5.555, P = 0.0061; sour: OR 3.267, 95% CI 1.491–7.160, P = 0.0031, respectively). Conclusions Sensitivity and response to specific food taste were associated with GERD. The results of a preference to hot or salty food and endoscopic esophagitis suggest that physical stimuli are important for esophageal injuries.